Domination And Revictimization Case Study On Victims Of Violence In Dating Relationship In Surabaya City - Alfa Nadia, Emma (Opción, 2019)
Dating relationships are inseparable from problems and the potential for con- flict leads to violence. Revictimization is a form of inequality of power relations and exploitation of women’s bodies, with narrative seduction and intimidation of coercion of the will to coercion of sexual relations in personal relations. This research method uses qualitative research. In this study, the author di- vide five categories of victimization: First Framing and Community Negative Stigma, Second Reason like liking to defend the actions of the perpetrators, Third Persuasion of love is victim vulnerability and recurs, Fourth Efforts to intimidation and Cyber Stalking, Fifth Post Court Decision. Women victims of courtship violence despite being able to be free and leave the relationship or courtship violence but still experience several other times of violence commit- ted by groups, immediate family, society and the law, this cycle of abuse makes victims feel in the complexity of violence that is never finished.